Faktor-Faktor Kesiapan Kerja Siswa Kelas XII SMK N 2 Semarang - Ayu Ardila; Sutrisno; Noni Setyorini (Yayasan Al Ma'arif Dawuhan, 2024)
This study aims to examine the influence of Adversity Quotient, Self-Efficacy, Learning Achievement, and Industrial Work Practice on the work readiness of grade XII students of SMK N 2 Semarang. The population of this study was 422 students from 12 classes and 6 majors, with a sample of 81 students taken using random sampling techniques. The data were analyzed using multiple linear regression to test the relationship between variables, both partially and simultaneously. The results showed that Adversity Quotient had a positive effect on students' work readiness with a significant value of 0.040 <0.05, Self-Efficacy had a positive effect with a significant value of 0.000 <0.05, Learning Achievement had a positive effect with a significant value of 0.007 <0.05, and Industrial Work Practice also had a positive effect with a significance value of 0.008 <0.05. Overall, the results of the F test showed that these four variables had a positive effect together on students' work readiness with a significance value of 0.000 <0.05. These findings indicate that the ability to face challenges, self-confidence, good academic achievement, and practical experience through industrial work practices together play an important role in improving students' work readiness. Therefore, the development of these four aspects is very important in preparing students to face the world of work.